2019
DOI: 10.1128/mcb.00329-19
|View full text |Cite
|
Sign up to set email alerts
|

ZFP281 Recruits MYC to Active Promoters in Regulating Transcriptional Initiation and Elongation

Abstract: The roles of the MYC transcription factor in transcriptional regulation have been studied intensively. However, the general mechanism underlying the recruitment of MYC to chromatin is less clear. Here, we found that the Krüppel-like transcription factor ZFP281 plays important roles in recruiting MYC to active promoters in mouse embryonic stem cells. At the genome scale, ZFP281 is broadly associated with MYC, and the depletion of ZFP281 significantly reduces the levels of MYC and RNA polymerase II at the ZFP281… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
1
13
0
1
Order By: Relevance
“…Although Nanog seems relatively density-insensitive during self-renewal, once mESCs are committed to differentiation in -LIF, Nanog protein levels decrease more at LD compared to HD ( Figure 1 I). We also observe more rapid loss of protein expression of pluripotency-related factors Sall4 and Zfp281 ( Luo et al., 2019 ; Pantier et al., 2021 ) at LD. Interestingly, Oct4, Sox2, and Klf5 were downregulated in a density-independent manner, and protein levels of E-cadherin and Zfp57 expression were maintained better in LD compared to HD.…”
Section: Resultsmentioning
confidence: 70%
“…Although Nanog seems relatively density-insensitive during self-renewal, once mESCs are committed to differentiation in -LIF, Nanog protein levels decrease more at LD compared to HD ( Figure 1 I). We also observe more rapid loss of protein expression of pluripotency-related factors Sall4 and Zfp281 ( Luo et al., 2019 ; Pantier et al., 2021 ) at LD. Interestingly, Oct4, Sox2, and Klf5 were downregulated in a density-independent manner, and protein levels of E-cadherin and Zfp57 expression were maintained better in LD compared to HD.…”
Section: Resultsmentioning
confidence: 70%
“…Studies show that H19 is highly associated with organ fibrosis, including liver fibrosis [ 96 ], lung fibrosis [ 124 ], renal fibrosis [ 56 ], and cardiac fibrosis [ 125 , 126 ]. Evidence has demonstrated that H19-mediated regulation of DUSP5 affects ERK1/2 phosphorylation, increasing cardiac fibroblast proliferation and fibrosis [ 127 ].…”
Section: Lncrna-h19 Regulates Cardiac Fibrosismentioning
confidence: 99%
“…Diagram highlighting prominent pre-and post-transcriptional interactions between NF-κB and the Lin28/let-7 pathways. Core components of the NF-κB activation pathway are impacted by let-7 miRNA levels [83,[97][98][99]107,121,122], and the Lin28/let-7 regulatory loops are governed by NF-κBdependent gene expression [83,84,95,96,[118][119][120]. While the net vector of NF-κB and Lin28/let-7 pathway interactions appears most often to result in a positive feedback loop, there are several key negative regulatory interactions posited as well.…”
Section: Conclusion Ongoing Questions Future Directionsmentioning
confidence: 99%
“…The Myc transcriptional regulator, a well-studied pluripotency gene, also plays a key role in upregulating the transcripts of both Lin28a and Lin28b [ 95 , 118 , 119 , 120 ]. The Myc transcript is, itself, post-transcriptionally repressed by let-7 miRNAs [ 121 , 122 ], meaning that Myc exists in a finely tuned circuit with Lin28 induction and consequent let-7 miRNA level reduction able to further induce Myc [ 95 ].…”
Section: Post-transcriptional-level Interactions Between Nf-κb Andmentioning
confidence: 99%